Head lice. - Scanni, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
The history of head lice strictly interlaces with the millionaire history of the human, supporting the evolutionist theory. In a disease characterized by a so long history, two new things emerge. The introduction on the market at the end of ’90ies of a product consisting of coconut extract, anise and ylang ylang oil revolutionized the market of pediculicides, so that from that event onwards no new products with neurotoxic activity were marketed, but only various versions of pediculicides with physical activity. The other novelty was the advent of entodermoscopy, a new science that allowed dermatologists to study in vivo the anatomy, physiology and biology of head lice, helping them in the difficult task of establishing the vitality of a colony of head lice.